2016
DOI: 10.1111/apa.13633
|View full text |Cite
|
Sign up to set email alerts
|

Being born large for gestational age is associated with earlier pubertal take‐off and longer growth duration: a longitudinal study

Abstract: Aim: Perinatal factors seem to influence the onset of puberty, but there is limited information on the potential effect of large size at birth on pubertal growth. This study evaluated pubertal growth in children born large for gestational age (LGA) compared to children born appropriate for gestational age (AGA).Methods: Longitudinal growth data collected from 70 children -40 AGA and 30 LGAwere analysed. The ages at take-off, peak height velocity, final height and pubertal growth spurts were calculated using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The initial search netted 18 968 titles, with 38 full texts included for review (Figure ) . These amounted to a total of 22 721 individuals, with 60% female representation.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search netted 18 968 titles, with 38 full texts included for review (Figure ) . These amounted to a total of 22 721 individuals, with 60% female representation.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper by Di Giovanni et al has shown that babies being large for GA (high birth weight) have earlier onset of pubertal growth, and a previous study by our research group found a linear negative correlation between BMI in childhood and onset of pubertal growth. 23,36 Higher weight at birth and higher BMI in the 1990 cohort might be related to earlier pubertal growth seen for girls in the later-born cohort, analogous to these two studies. Compared with the former Swedish growth reference of individuals born in 1956, the 1974 cohort showed earlier mid-pubertal growth.…”
Section: Discussionmentioning
confidence: 57%
“…Our finding of inverse associations of LGA with adolescent metabolic traits are consistent with a study of 18,288 adolescents and adults with the same metabolomics platform as our study (52) which showed a higher mean birth weight across the distribution was associated with healthier lipid profile, including lower triglycerides, and other lipids that we see inverse associations of LGA with in our study. This may reflect an interplay with offspring adiposity and puberty whereby LGA offspring have higher prepubertal body fat compared to AGA (53) with this leading to earlier puberty for LGA (54, 55) which in turn might influence metabolic traits (56). This may also explain our finding that the association between LGA and healthier metabolic profile was weakened or even reversed by early midlife (since all AGA offspring should have already completed puberty).…”
Section: Discussionmentioning
confidence: 99%